An accurate procedure to describe colors in taxonomic works, with an example from Ichneumonidae (Hymenoptera) - Aguiar, Alexandre P. (Zootaxa, 2005)
The use of the RGB color system is suggested as a desirable option to increase accuracy of color descriptions in taxonomic works, and two techniques are proposed to allow the conversion of observed colors into RGB formulas: direct comparison with colors generated on a computer screen, and color sampling from digital images of the specimens, through commonly used illustration software. Equipment and software costs are considered the main limitations, but stability, reproducibility, objectiveness, prompt visualization, and the null influence of surrounding colors on colors displayed on a computer screen are recognized as major advantages justifying the adoption of the procedure.